A Scientific Review on Disabled-Friendly Educational Environment for Disabilities Student in Malaysia - Ismail, Faisal Husen; Mohammad, Che Adenan; Nirwana, Andri; Abu Hassan, Muhammad Ikram; Masruri, Muhammad (Journal of Techno-Social, 2023)
The increase in the number of Persons with Disabilities (OKU) in Malaysia as registered in the Department of Social Welfare (JKM) until the end of 2020 is estimated to be 570,000 and needs attention. People with disabilities are a part of Malaysian society and need to be given equal rights and given the opportunity to go through life easily. However, achieving the right to equality is not a simple thing to achieve today. There are many factors and challenges faced by people with disabilities due to negative attitudes and discrimination that have been ingrained in society. So, this study wants to explore facilities and equality in the field of disabled-friendly higher education. This study presents an exploratory study from selected past studies related to higher education for students with special needs in Malaysia. The research uses the choice approach of 10 selected articles to explore the problems, management, and implementation of efforts to create a friendly environment for people with disabilities. This study found that educational facilities at the higher education level have been created, such as facilities for parking spaces specially built for the disabled. This study suggests the need for improvements to other infrastructures, such as wheelchair access facilities, special pathways for the blind, and so on. The success of disabled-friendly higher education needs to involve a proactive environment in combating the neglect of disabled people in the current national development. Hopefully, this idea can contribute to building an inclusive environment in an educational institution. This study suggests future research related to aspects of community morality towards the disabled.